A Thyroid Cytology Experience: The Comparision of Cytological and Histopathological Findings (Annals of Medical Research, 2021)
Aim: Thyroid fine needle aspiration cytology (FNAC) is a common technique used for the follow-up and diagnosis of nodules. FNAC is used for differentiating between benign and malignant lesions preoperatively, and therefore, is helpful to determine the type of surgery. The aim of this study is to screen cases that have been evaluated for thyroid cytology and thyroid surgery specimens in our department, and to investigate the experience of the diagnosis using thyroid fine needle aspiration cytology.
Keywords: Fine Needle Aspiration Cytology; Histopathology; Thyroid.